Biology and host range testing of Triarthria setipennis and Ocytata pallipes (Diptera: Tachinidae) for the control of the European earwig (Forficula auricularia). Issue 4 (2nd April 2016) - Maczey, Norbert; Edgington, Steve; Moore, Dave; Haye, Tim
ABSTRACT: The European earwig ( Forficula auricularia ) is an invasive species in the Falkland Islands, causing considerable problems for local horticulture, as well threatening indigenous ecosystems. To assess the potential of a classical biological control introduction two parasitoid fly species, Triarthria setipennis and Ocytata pallipes (Diptera: Tachinidae), were collected from sites in southern and northern England and then tested for their suitability as earwig biological controls at Egham, UK. Both species had previously been introduced into North America for earwig control however little is known of their long-term efficacy and host specificity. Host range tests including both target and non-target species were done. As there are no native Dermaptera on the Falkland Islands, tests were restricted to the field cricket Gryllus assimilis and the Dubia cockroach Blaptica dubia, as representatives of insect orders phylogenetically closely related to earwigs. A second cricket species ( Gryllus bimaculatus ) was included in an egg-depositing experiment for O. pallipes . Both tachinid species successfully parasitised and emerged from earwigs under laboratory conditions but no signs of parasitisation and development were observed in either the cricket or cockroach.